Acute changes in preload and the QRS amplitude in advanced heart failure patients. (3rd June 2019) - Dual, Seraina Anne; Pergantis, Panagiotis; Schoenrath, Felix; Keznickl-Pulst, Julian; Falk, Volkmar; Meboldt, Mirko; Daners, Marianne Schmid
Abstract: To date, only invasive monitoring methods are available for continuous monitoring of the volume status of heart failure (HF) patients. The literature suggests that left ventricular (LV) volume status can in part be deduced from the electrocardiogram in healthy individuals in the experimental setting. The aim of this study was to evaluate if short-term changes in cardiac preload can be deduced from the QRS amplitude in advanced HF patients. We examined 19 non-decompensated advanced HF patients, listed for heart transplantation or in the process of evaluation for advanced HF treatment, during a leg raising maneuver. Electrocardiac (leads I, II, and V6) data was collected continuously in all patients along with preload indicators available in every specific patient: central venous pressure (n = 11), pulmonary arterial pressure (n = 9), pulmonary wedge pressure (n = 9), mitral inflow Doppler wave velocity (E- wave) (n = 17), and LV volume (n = 7). During leg raising, the increase of cardiac preload was significant with an increase in the E wave of 0.09 m s −1 (p = 0.029), but a change in LV volume or the QRS amplitude was not observed. In patients with a Swan-Ganz catheter, however, a statistically significant negative correlation between the mean pulmonary arterial pressure and the QRS amplitude in V6 and II was found with correlation coefficient (R) and 95% confidence intervals of R = −0.28 (−0.49, −0.04) and R = −0.29 (−0.50, −0.05), respectively. Although the identified correlation is not very strong, the findings of this study in advanced HF patients are in accordance with experimental data recorded in healthy individuals. The findings support the further investigation in settings where greater, acute LV volume changes are probable, such as in HF patients with mechanical circulatory support.